Novel pathogenic variants in KIT gene in three Chinese piebaldism patients - Wang, Chen; Zhang, Yingzi; Hu, Xuyun; Wang, Lijuan; Xu, Zhe; Xing, Huan (Frontiers in Medicine, 2022)
Background Piebaldism is a rare autosomal dominant disease, and roughly 75% patients had KIT gene mutations. Up to date, approximately 90 KIT mutations causing piebaldism were reported. Methods To identify KIT gene mutations in three pediatric piebaldism patients from different families and explore the genotype-phenotype correlation, peripheral blood DNA were collected from probands and their parents. Whole-exome sequencing was performed to detect potential disease-causing variants in the three probands. Putative variants were validated by Sanger sequencing. Results Heterozygous variants of c.2469_2484del (p.Tyr823*), c.1994G > C (p.Pro665Leu), and c.1982_1983insCAT (p.662_663insIle) in KIT gene were detected in three probands. These variants were all novel and classified as pathogenic/likely pathogenic variants according to the interpretation guidelines of American College of Medical Genetics and Genomics and the Association for Molecular Pathology. The probands carrying variants located in tyrosine kinase domain exhibited a more severe phenotype. Conclusion The piebaldism in three families was caused by novel heterozygous KIT variants. The severity of phenotypes is related with the types and locations of different mutations. Our results further provided evidence for genetic counseling for the three families.